Planning of tunneling projects using computer simulation and fuzzy decision making - Abdallah, Moatassem; Marzouk, Mohamed (Journal of Civil Engineering and Management, 2013)
Tunnel construction is one of the important infrastructure projects, which is vital for enhancing the transportation networks, especially in congested cities. Tunnel projects are characterized by long durations, large budgets, complexities, repetitive construction tasks, risks, and uncertainties. Several construction techniques have been developed in the tunnel construction industry to improve the constructability of tunnels and decrease the impact on surrounding structures. This paper presents a framework for planning tunnel construction using computer simulation. The proposed tool aids contractors in estimating the required time and cost for construction. Five tunnel construction techniques have been considered in the development of this tool with different ground supporting techniques. The proposed framework consists of three modules: (1) tunnel analyzer module, (2) simulation module, and (3) decision support module, and is capable of selecting the best construction technique using fuzzy group decision-making method based on time, cost and other selection criteria that could be defined during the decision-making phase. This decision method ranks alternatives based on a group of experts and a predefined set of criteria. Numerical examples are introduced to illustrate the capabilities of the proposed framework.